Imigração espanhola na Amazônia: as colônias agrícolas e o desenvolvimento socioeconômico do Nordeste paraense (1890-1920) - SMITH JÚNIOR, Francisco Pereira (Universidade Federal do Pará, 2013)
The period among the years of 1880 and 1920 marked the history of the international migrations in the State of Pará. With the strong migration propaganda in Europe, the State of Pará was the stage entrance for many European immigrants, among them, the Spanish. Attracted by agriculture which was in a high position in the state, due to the creation of colonial settlements, several Spanish families, coming many times from poor settlements, crossed the Atlantic and reconstructed their lives in various colonial centers of the State of Pará. Thus, this study is to investigate which socio-economic contributions of Spanish immigrants to the development of northeastern. From now on, it is possible to understand all the process of introduction of these settlers in Pará territory and their daily lives in the settlement, with the use of official documents and interview to demonstrate this experience of Spanish in Amazon. With this, pretend to give a contribute to research the field of historiographical studies on international migration in the Amazon, considering that there is still shortage of work in the migration studies in the region, except for some works recognized by researchers who dedicated themselves to the theme of migration in the paraense territory.